2018
DOI: 10.1186/s13068-018-1163-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid organosolv: steam explosion method for the efficient fractionation and pretreatment of birch biomass

Abstract: BackgroundThe main role of pretreatment is to reduce the natural biomass recalcitrance and thus enhance saccharification yield. A further prerequisite for efficient utilization of all biomass components is their efficient fractionation into well-defined process streams. Currently available pretreatment methods only partially fulfill these criteria. Steam explosion, for example, excels as a pretreatment method but has limited potential for fractionation, whereas organosolv is excellent for delignification but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 58 publications
(55 reference statements)
6
75
0
1
Order By: Relevance
“…Some enzyme and substrate pairs are given in Table 7 with the effect of increasing substrate concentration. The agricultural residues (corn stover, Kumar and Wyman (2008) GC-220 Cellulose Increased with increase in conc Kumar and Wyman (2008) Cellulase Avicel Decreased with increase in conc Eckard et al (2013) Cellulases Pretreated forest wood Increased with increase in conc Matsakas et al (2018) Celluclast 1.5 L T. reesei Corn stover and corn fiber Increased with increase in conc Arantes and Saddler (2011) Cellic CTec 2 High CrI cellulose Increased with increase in conc Li et al (2018) corn fiber, rice husk, wheat straw, etc.) needs considerably lower protein loadings to achieve optimum adsorption than the forestry residues (poplar, Douglas fir and lodgepole pine).…”
Section: Concentrationmentioning
confidence: 99%
“…Some enzyme and substrate pairs are given in Table 7 with the effect of increasing substrate concentration. The agricultural residues (corn stover, Kumar and Wyman (2008) GC-220 Cellulose Increased with increase in conc Kumar and Wyman (2008) Cellulase Avicel Decreased with increase in conc Eckard et al (2013) Cellulases Pretreated forest wood Increased with increase in conc Matsakas et al (2018) Celluclast 1.5 L T. reesei Corn stover and corn fiber Increased with increase in conc Arantes and Saddler (2011) Cellic CTec 2 High CrI cellulose Increased with increase in conc Li et al (2018) corn fiber, rice husk, wheat straw, etc.) needs considerably lower protein loadings to achieve optimum adsorption than the forestry residues (poplar, Douglas fir and lodgepole pine).…”
Section: Concentrationmentioning
confidence: 99%
“…A review on the use of organosolv pretreatment for the delignification of lignocellulosic materials in the last two years showed that an S/L ratio of 1:10 predominated [8]. Exceptions include the works carried out by Matsakas et al [36] using silver birch wood chips, by Patel et al [37] using Norway spruce, and by Yuan et al [38] using corn stover, wherein an S/L ratio of 1:2 was used. Research works in the literature reported lignin-rich fractions containing >90% lignin [8] achieved via different organosolv pretreatment strategies, namely HCl-catalyzed tetrahydro-2-furanmethanol pretreatment of eucalyptus [39], auto-catalyzed ethanol pretreatment of Eucalyptus nitens bark [40], and oxalic acid-catalyzed glycerol pretreatment of sugarcane trash [41].…”
Section: Discussionmentioning
confidence: 99%
“…Steam explosion has been demonstrated to be more effective than other pretreatments. Some of the researches are showing a combination of pretreatment methods to improve delignification . Some examples of effectiveness are commented in Table .…”
Section: Organic Solventsmentioning
confidence: 99%
“…Some of the researches are showing a combination of pretreatment methods to improve delignification. 63,64 Some examples of effectiveness are commented in Table 4.…”
Section: Steam Explosion (Se)mentioning
confidence: 99%